EFEKTIVITAS PENDEKATAN BERDIFERENSIASI MELALUI IMPLEMENTASI MODEL PEMBELAJARAN PJBL TERHADAP HASIL BELAJAR SISWA PADA MATERI HARMONI DALAM EKOSISTEM DI KELAS V SD MUHAMMADIYAH 3 MAKASSAR - Aulia, Ifa; Erwinto imran, Muh; Amin said, Muhammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to assess the effectiveness of implementing a differentiated learning approach through the Project-Based Learning (PjBL) model on student learning outcomes in the subject of harmony in ecosystems in fifth-grade students at Muhammadiyah 3 Elementary School, Makassar. This study employed a quantitative method with a pre-experimental One Group Pretest–Posttest Design. The subjects were all 14 fifth-grade students, using a purposive sampling technique. Data collection was conducted through tests, observations, and documentation. Data analysis used statistical tests to determine differences in learning outcomes before and after the treatment. The results showed an increase in student learning outcomes after the implementation of differentiated learning based on PjBL, as evidenced by the significant increase in pretest and posttest scores. Therefore, it can be concluded that the differentiated learning approach through the Project-Based Learning model is effective in improving student learning outcomes in the subject of harmony in ecosystems.